Theoretical study of the low-lying electronic states of magnesium sulfide cation including spin–orbit interaction. (November 2017) - Chen, Peng; Wang, Ning; Li, Song; Chen, Shan-Jun
Highlights: High level computations with the inclusion of spin–orbit coupling are employed. Geometrical structures and spectroscopic properties are predicted. Radiative transition probabilities and lifetimes are reported. The photoelectron spectrum has been simulated. Capable of supporting further experimental and theoretical researches. Abstract: Highly correlated ab initio calculations have been performed for an accurate determination of electronic structures and spectroscopic features for the low-lying electronic states of the MgS + cation. The potential energy curves for the four Λ-S states correlating to the lowest dissociation asymptote are studied for the first time. Four Λ-S states split into nine Ω states through the spin–orbit coupling effect. Accurate spectroscopic constants are deduced for all bound states. The spin–orbit couplings and the transition dipole moments, as well as the PECs, are utilized to calculate Franck–Condon factors and radiative lifetimes of the vibrational levels. To verify our computational accuracy, analogous calculations for the ground state of MgS are also carried out, and our derived results are in reasonable agreement with available experimental data. In addition, photoelectron spectrum of MgS has been simulated. The predictive results are anticipated to serve as guidelines for further researches such as assisting laboratorial detections and analyzing observed spectrum.